Empowering Capacity Building – The Implementation and Impacts of the EMVITET Project - Kunnari, Irma; Maetoloa, Katja (Journal of Technical Education Science, 2022)
The path towards Education 4.0 in Vietnam requires new mindsets and new competencies of teachers and educational institutions. In the Empowering Vietnamese VET Teachers for Transformation towards Education 4.0 (EMVITET) Capacity Building in Higher Education Erasmus+ project, Education 4.0 competencies in pedagogy, digital technologies and learning ecosystems were developed during a three-and-a-half-year process (2019–2022). Six Vietnamese educational institutions participated in the project and three European universities provided the facilitation of the process. This article describes how the EMVITET project was designed and implemented to create an empowering and effective learning process by utilising a participatory and collaborative approach. The other aim is to illustrate the impacts and implications of the project and draw conclusions on how to build a sustainable learning ecosystem for Education 4.0 in Vietnam.